Arrays of ultra-thin selenium-doped zirconium-anodic-oxide nanorods as potential antibacterial coatings - Kamnev, Kirill; Bendová, Mária; Fohlerová, Zdenka; Fialová, Tatiana; Martyniuk, Oleh; Prášek, Jan; Číhalová, Kristýna; Mozalev, Alexander (ROYAL SOC CHEMISTRY, 2025)
Two characteristic types of extraordinarily thin upright-standing ZrO2-based nanorods self-aligned on a substrate, differing in diameters (20/30 nm), lengths (90/120 nm), and population densities (1.1/4.6 × 1010 cm2), were synthesized via the porous-anodic-alumina (PAA)-assisted anodization of Zr in 1.5 M selenic acid followed by selective PAA dissolution. A needle-like shape was achieved due to the unique formation of zirconium anodic oxide in extremely thin nanopores that grow only in selenic acid. The SEM, XPS, and Raman spectroscopy analyses revealed that the nanorods feature a core/shell structure in which the core is stoichiometric amorphous ZrO2, and the shell is 6 nm thick hydroxylated zirconium dioxide ZrO2x(OH)2x mixed with Al2O3. The core and shell incorporated electrolyte-derived selenate (SeO42) ions, which replace up to 1% of the O2 ions in the nanorod surface layer. Besides, nanoparticles of elemental Se were deposited on the top of rods during anodic polarization. A model was developed for the cooperative ionic transport and electrochemical and solid-state reactions during the PAA-assisted growth of zirconium oxide in selenic acid. The two Se-doped top-decorated zirconium-oxide nanorod arrays were examined as potential antibacterial nanomaterials toward G-negative E. coli and G-positive S. aureus, using direct SEM observations of the bacteria–surface interfaces and carrying out the modified Japanese Industrial Standard test for antimicrobial activity and efficacy, JIS Z 2801. While specific differences in interaction with each type of bacteria were observed, both nanostructures caused a significant harmful synergetic effect on the bacteria, acting as non-metallic (Se) ion-releasing bactericidal coatings along with repellent and contact-killing activities arising from extraordinary needle-like nanoscale surface engineering.

Two characteristic types of extraordinarily thin upright-standing ZrO2-based nanorods self-aligned on a substrate, differing in diameters (20/30 nm), lengths (90/120 nm), and population densities (1.1/4.6 × 1010 cm2), were synthesized via the porous-anodic-alumina (PAA)-assisted anodization of Zr in 1.5 M selenic acid followed by selective PAA dissolution. A needle-like shape was achieved due to the unique formation of zirconium anodic oxide in extremely thin nanopores that grow only in selenic acid. The SEM, XPS, and Raman spectroscopy analyses revealed that the nanorods feature a core/shell structure in which the core is stoichiometric amorphous ZrO2, and the shell is 6 nm thick hydroxylated zirconium dioxide ZrO2x(OH)2x mixed with Al2O3. The core and shell incorporated electrolyte-derived selenate (SeO42) ions, which replace up to 1% of the O2 ions in the nanorod surface layer. Besides, nanoparticles of elemental Se were deposited on the top of rods during anodic polarization. A model was developed for the cooperative ionic transport and electrochemical and solid-state reactions during the PAA-assisted growth of zirconium oxide in selenic acid. The two Se-doped top-decorated zirconium-oxide nanorod arrays were examined as potential antibacterial nanomaterials toward G-negative E. coli and G-positive S. aureus, using direct SEM observations of the bacteria–surface interfaces and carrying out the modified Japanese Industrial Standard test for antimicrobial activity and efficacy, JIS Z 2801. While specific differences in interaction with each type of bacteria were observed, both nanostructures caused a significant harmful synergetic effect on the bacteria, acting as non-metallic (Se) ion-releasing bactericidal coatings along with repellent and contact-killing activities arising from extraordinary needle-like nanoscale surface engineering.
Arrays of ultra-thin selenium-doped zirconium-anodic-oxide nanorods as potential antibacterial coatings
Keywords: anodizing; zirconium oxide; biomedical application; anodizing; zirconium oxide; biomedical application